2021
DOI: 10.1080/08974438.2021.1936332
|View full text |Cite
|
Sign up to set email alerts
|

Meat Consumption in Transition: The Case of Crisis Region of Iraqi Kurdistan

Abstract: In recent decades, meat consumption patterns have been changing. This study investigates the main drivers of white and red meat consumption in crisis regions based on microeconomic theory, hegemonic masculinity theory, meat paradox theory, and nutrition transition theory. A quantitative questionnaire survey was conducted in Sulaymaniyah city in Iraqi Kurdistan in 2018. Data from 233 respondents were collected. Multifactorial linear regression analysis showed that the main drivers in the consumption of white me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…The data from this study showed that the respondents mostly purchase and consume whole chicken freshly slaughtered on-site in the wet markets, which can be related to the consumers' taste and freshness preference that has previously been shown by Neima et al (2021); and Abdalla et al (2021) by finding positive and statistically significant relationships between the taste of chicken and white meat consumption in Sulaymaniyah City. This can prove the success of the wet market as a common small business found in almost every quarter in Sulaymaniyah city.…”
Section: Discussionsupporting
confidence: 52%
“…The data from this study showed that the respondents mostly purchase and consume whole chicken freshly slaughtered on-site in the wet markets, which can be related to the consumers' taste and freshness preference that has previously been shown by Neima et al (2021); and Abdalla et al (2021) by finding positive and statistically significant relationships between the taste of chicken and white meat consumption in Sulaymaniyah City. This can prove the success of the wet market as a common small business found in almost every quarter in Sulaymaniyah city.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, per capita consumption of red meat in the Sulaymaniyah governorate between 2011 to 2018 has climbed up from 4.9 kg in 2011 to 14.9 in 2014, then in 2018 it dropped to 11.8 kg (Neima and Hassan, 2020). These fluctuations are mostly linked to the per capita income in the Kurdistan region and an increase in the price of meat, as it was previously proven that income has an excessive influence on the demand for meat (Abdallaa et al, 2021;Thornton, 2010;Akbay and Boz, 2005).…”
Section: Per Capita Broiler Chicken Meat Consumptionmentioning
confidence: 89%
“…Accordingly, the increase in poultry meat demand has started after the economy boomed in the region after 2003, which left a big gap between demand and local agricultural production and led to an increase in food imports from abroad (World Bank, 2019). According to Abdallaa et al, (2021) meat consumption, in the KRI, is positively influenced by the growth in household income.…”
Section: Introductionmentioning
confidence: 99%
“…According to a French study [ 76 ], the decline in meat consumption may be caused by concerns about its impact on one’s health and the natural environment (including animal welfare). On the other hand, research conducted in Iraqi Kurdistan [ 77 ] showed the opposite tendency, indicating that animal welfare does not have a statistically significant effect on the consumption of any type of meat. In turn, studies conducted in Spain [ 78 ] showed that the risk of cancer and increased mortality resulting from meat consumption also does not significantly reduce its consumption.…”
Section: Discussionmentioning
confidence: 99%